Setting up a school museum (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
The creation of a school museum offers an opportunity for a school and its broader community to celebrate the institution’s no doubt unique history and heritage, and to offer an “open book to the world” of its history, contribution to society and its character. Whilst professional museum planners might be employed to take on the task of managing the overall project and tackling the rather daunting list of “To Do’s”, their services are expensive, and might cause a school’s Governing Body to balk at the anticipated costs. In this article, Pietermaritzburg teacher, Matthew Marwick, summarises the journey undertaken by the members of the Museum Planning Committee at Maritzburg College, as they upgrade the school’s existing museum, which currently is primarily made up of ad hoc displays of photos and memorabilia, in the build-up to the school’s 150th celebrations in 2013. In the article, he points out some of the difficulties already experienced during this venture (which is ongoing), and offers practical advice to educators who might be considering a similar undertaking.
Keywords: School museum; Heritage preservation; Museum planning; Maritzburg College; School History research